2023
DOI: 10.1111/srt.13405
|View full text |Cite
|
Sign up to set email alerts
|

The effect of secukinumab treatment for psoriasis on serum cytokines and correlation with disease severity

Abstract: Objective: To investigate the effects of secukinumab treatment for psoriasis on different functional cytokines and inflammatory mediators in patients' serum Methods: Enzyme-linked immunosorbent assay was used to detect interleukin (IL)-1β and IL-1RA associated with intrinsic immunity; IL-6, IL-18, and growth regulated oncogene alpha (GROα) associated with neutrophils; IL-12, tumour necrosis factor (TNF)-α, and interferon (IFN)-γ associated with Th1; IL-23, IL-17A, and IL-22 associated with Th17; Thymus activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…In light of our hypothesis, this could be potentially detrimental if IL-17 is blocked. Furthermore, in patients with ankylosing spondylitis, the use of SCK did not decrease Th2 cells 55 , paralleling recent findings in psoriatic patients 56 . In contrast, in our study we observed a significant decrease in Th2 cells.…”
Section: Discussionsupporting
confidence: 85%
“…In light of our hypothesis, this could be potentially detrimental if IL-17 is blocked. Furthermore, in patients with ankylosing spondylitis, the use of SCK did not decrease Th2 cells 55 , paralleling recent findings in psoriatic patients 56 . In contrast, in our study we observed a significant decrease in Th2 cells.…”
Section: Discussionsupporting
confidence: 85%
“…However, not all studies are coherent regarding secukinumab's effect on the level of this alarmin. A study by Wu et al showed higher serum levels of hBD2 after treatment with secukinumab than in a normal population [228]. Another study by Cardner et al analyzed the serum levels of beta-defensin in 2000 patients with psoriatic arthritis in a placebo-controlled phase-III clinical trial of secukinumab.…”
Section: Defensinsmentioning
confidence: 99%